Peran Logistik dan Transportasi Dapat Meningkatan Efesiensi Kemudahan Dalam Pengiriman Barang Di Indonesia - Khalistia, Natasya Putri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Purpose : The purpose of this journal is to illustrate howlogistics and transportation can improve the efficiency of goodsdelivery in Indonesia. The research aims to providerecommendations for stakeholders in developing strategies thatcan improve the efficiency of logistics and transportation,which is important for economic activities in Indonesia.Method : This research uses the literature study method toexamine the role of logistics and transportation in improvingthe efficiency of freight forwarding in Indonesia. Datacollection was conducted through a systematic search ofvarious academic databases, digital libraries, and governmentarchives to identify relevant publications, including journalarticles, industry reports, theses, and dissertations.Result : The logistics and transportation sector in Indonesia isan important pillar for economic growth and meeting people'sneeds. Investments in technology and infrastructure,coordination between industry players, and the selection ofefficient modes of transportation all contribute to improving theefficiency of shipping goods. Cooperation between thegovernment and the private sector in the development of thissector is crucial to improving the quality of life andstrengthening Indonesia's position in the global market. Thismarks the logistics and transportation sector as key tosustainable economic growth and national economicresilience.